Late Genitourinary Toxicity Outcomes in 300 Prostate Cancer Patients Treated With Dose-escalated Image-guided Intensity-modulated Radiotherapy. Issue 9 (September 2017) - Byrne, K.; Hruby, G.; Kneebone, A.; Whalley, D.; Guo, L.; McCloud, P.; Eade, T.
Abstract: Aims: To quantify and qualify late genitourinary toxicity in a cohort of patients with localised prostate cancer treated with image-guided intensity-modulated radiotherapy (IMRT) to doses ≥78 Gy. Materials and methods: The cohort consisted of 300 patients treated with definitive dose-escalated IMRT between 2007 and 2013. Ninety-seven patients received 78–80 Gy in 38 fractions, and 203 received 82–84 Gy in 40 fractions. International Prostate Symptoms Score (IPSS) and supplemental quality of life data were recorded at baseline, weekly during treatment and at follow-up. Genitourinary toxicities were recorded using modified Radiation Therapy Oncology Group criteria during weekly treatment review and at each follow-up. Kaplan–Meier curves were used to assess the cumulative incidence of grade ≥ 2 genitourinary toxicity at 3 years. Baseline patient characteristics and symptoms were then used in univariate and multivariate analyses to identify predictors of late urinary toxicity. Results: The median follow-up was 58 months (range 9–109 months). The actuarial cumulative 3 year rates of grade ≥ 2 and grade 3 genitourinary toxicity were 14.9% and 2.8%, respectively. There was no grade 4 toxicity. History of transurethral resection of the prostate (TURP), alpha blocker use before radiation, any hormone use, baseline IPSS ≥ 14 and pre-existing incontinence or nocturia were significantly associated with late ≥ 2 genitourinary toxicity on univariate analysis. On multivariate analysis, only previous TURP retained significance, with a hazard ratio of 2.54 ( P  = 0.002). Conclusion: Our study showed acceptable levels of late grade 2 genitourinary toxicity and low rates of late grade 3 genitourinary toxicity in a cohort of patients with prostate cancer treated with image-guided IMRT to doses between 78 and 84 Gy. Variables associated with increased late ≥ 2 genitourinary toxicity include previous TURP, alpha blocker use, hormone use and pre-existing urinary dysfunction. Highlights: Late genitourinary toxicity data evaluated in prostate cancer patients undergoing definitive radiotherapy. Late grade ≥ 2 and grade 3 genitourinary toxicity were acceptable at 3 and 5 years. Late ≥ 2 genitourinary toxicity linked with several variables on univariate analysis. These include alpha blocker use, baseline genitourinary dysfunction, transurethral resection of the prostate (TURP) and hormonal use. A previous TURP remained significant for late genitourinary toxicity on multivariate analysis.